Karakterisasi Bakteri Endofit Tanaman Sirih Timor (Piper betle L.) Penghasil Antibakteri - Gergonius Fallo; Lukas Pardosi; Anjelina M. da Cruz (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
Indonesia has a wealth of various types of plants that are useful as traditional medicinal plants. One of the medicinal plants that are often used by Indonesian people, especially on the island of Timor, East Nusa Tenggara (NTT) Province, is betel plant (Piper betle L.). Isolation of endophytic bacteria using the scratch method and the scatter method. The results of the isolation obtained 9 isolates. The results of the characterization of 9 isolates had round colonies, small, medium, large, flat elevation, and clear white color. The results of the bacterial test showed that 3 isolates had the potential as antibacterial, namely: SDE01, SAE03 and SBE04 isolates. Of the three isolates, SBE04 isolates had inhibition zone diameters of 1.7 and 1.35 mm against Escherichia coli and Staphylococcus aureus.Key words: antibacterial; endophytic bacteria; characterization; P. betle.